How family status and social security claiming options shape optimal life cycle portfolios - Andreas Hubener; Raimond Maurer; Olivia S. Mitchell (Goethe University Frankfurt, Center for Financial Studies (CFS), 2013)
Household decisions are profoundly shaped by a complex set of financial options due to Social Security rules determining retirement, spousal, and survivor benefits, along with benefit adjustments that vary with the age at which these are claimed. These rules influence optimal household asset allocation, insurance, and work decisions, given life cycle demographic shocks such as marriage, divorce, and children. Our model generates a wealth profile and a low and stable equity fraction consistent with empirical evidence. We also confirm predictions that wives will claim retirement benefits earlier than husbands, while life insurance is mainly purchased by younger men. Our policy simulations imply that eliminating survivor benefits would sharply reduce claiming differences by sex while dramatically increasing men's life insurance purchases.
urn:nbn:de:hebis:30:3-324844
Keywords: 330